PENGARUH PENGGUNAAN MEDIA INTERAKTIF BERBASIS QUIZLET DALAM MENINGKATKAN PENGUASAAN MUFRODAT - Auly Rif’atul Ma’Rifah; Muhammad Syaifullah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2026)
This study aims to determine the effect of using the Quizlet application on students' mastery of Arabic vocabulary. The study employs a quantitative approach using a quasi-experimental design specifically, a pretest-posttest control group design. The research sample consists of two classes an experimental class and a control class each comprising 15 students. The experimental class received instruction using the Quizlet application, while the control class utilized conventional teaching methods. Data collection was conducted using pre-test and post-test assessments. The data were analyzed using the SPSS program, employing normality tests, homogeneity tests, Paired Sample T-tests, and Independent Sample T-tests. The results indicate that the average student score in the experimental class increased from 54.33 to 82.53, whereas in the control class, it increased from 55.27 to 65.60. The normality test results indicate that the data are normally distributed, and the homogeneity test results show that the data are homogeneous. Furthermore, the Paired Sample T-Test results show a significance value of 0.000 (< 0.05), indicating a significant improvement in learning outcomes for each group. The Independent Sample T-Test results also show a significance value of 0.000 (< 0.05), with a mean difference of 16.933. Thus, it can be concluded that the use of the Quizlet application has a significant effect and is more effective than conventional methods in improving Arabic vocabulary mastery among seventh-grade students at MTs Darun Nasyiin.